2019
DOI: 10.1136/bmjopen-2019-031515
|View full text |Cite
|
Sign up to set email alerts
|

Which factors determine treatment choices in patients with advanced kidney failure? a protocol for a co-productive, mixed methods study

Abstract: IntroductionKidney disease is common, affecting up to 1 in 10 of the adult population, and the numbers are expected to rise over the next decade. There are three main treatments that are available to patients with kidney disease: transplantation, dialysis and supportive care without dialysis. Dialysis can occur in a dialysis unit or in a person’s home, but unit-based dialysis remains the most common initial treatment for patients in Wales. This is a cause for concern as most studies suggest that it is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…This was a qualitative study using the framework method [20] of data collection and analysis and reported using the Consolidated Criteria for Reporting Qualitative published elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a qualitative study using the framework method [20] of data collection and analysis and reported using the Consolidated Criteria for Reporting Qualitative published elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%
“…Gaining a better understanding of the factors that impact on treatment choices, and specifically to better understand why so many patients default to centre-based dialysis was the aim of the 'Dialysis Options and Choices Study' [19]. This two-year mixed method co-productive study integrated analysis of electronic renal patient records with documentary analysis of pre-dialysis education programmes, interviews with pre-dialysis patients and their families, and interviews with renal professionals, and a health economics analysis of dialysis modalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question was interpreted for this study as ‘assessing the efficacy of coproduction to better understand the barriers to home dialysis and map alternate pathways’. Full details of the overall study are available in the published protocol 49 . We summarize the overall study in Figure 1 and at the same time highlight the specific health service improvement and coproduction elements that this paper focusses on.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the overall study are available in the published protocol. 49 We summarize the overall study in Figure 1 and at the same time highlight the specific health service improvement and coproduction elements that this paper focusses on. The objective of this study was to ‘assess the efficacy of co‐productive research in chronic kidney disease service improvement to achieve greater sustainability’.…”
Section: Methodsmentioning
confidence: 99%